The impact of public transport service quality indicators on the intention to reuse the service: A study of a sample of customers of the Setram Constantine company - Massika Brahimi (Journal of Excellence for Economics and Management Research, 2026)
This study aims to determine the impact of transport service quality indicators on the intention to reuse Constantine tramway services. To achieve this objective, a descriptive-analytical approach was employed. A questionnaire was distributed to a sample of 216 tramway passengers, and the data were analyzed using the Statistical Package for the Social Sciences (SPSS). The results showed a statistically significant impact of transport service quality on the intention to reuse Constantine tramway services. The indicators (service provision, information availability, timeliness, comfort, and environmental impact) all had an effect on the respondents' intention to reuse the tramway, while the indicators (accessibility, customer care, and safety) did not have a statistically significant effect. Finally, the study offered several suggestions for improving transport service quality